Fast Coriolis mass flow metering for monitoring diesel fuel injection - Leach, F; Karout, S; Zhou, F; Tombs, M; Davy, M; Henry, M (Elsevier, 2017)
Prism signal processing is a new recursive FIR technique that facilitates the rapid tracking of sinusoidal signals, such as those used in a Coriolis Mass Flow Meter (CMFM). A Prism-based CMFM prototype has been developed using a commercial flowtube and a dual ARM processor-based transmitter, which is capable of generating flow measurement updates at 48 kHz. This has been applied in a feasibility study to the tracking of fast (e.g. 1.5 ms) injections of diesel fuel on a laboratory rig at engine speeds of up to 4000 rpm equivalent and at fuel pressures of up to 100 MPa. Due to the high level of vibration in the system, Prism-based notch filtering is used to suppress undesired modes of flowtube vibration in the sensor signal. Individual flow pulses can be detected by the system, but the relatively long period of oscillation of the flowtube compared to the fuel injection duration results in a spreading out over time of each flow pulse measurement. More precise measurement results may be obtained using a higher frequency resonant flowtube.